Tussah silkmoth pupae improve anti-tumor properties of Cordyceps militaris (L.) Link by increasing the levels of major metabolite cordycepin. Issue 10 (13th February 2019) - Wen, Zhixin; Du, Xingfan; Meng, Nan; Li, Yajie; Mi, Rui; Li, Xuejun; Sun, Yongxin; Ma, Shuhui; Li, Shuying
Abstract : Tussah silkmoth pupae improved the metabolic profile of Cordyceps militaris (L.) Link by upregulating 3-deoxyadenosine (with anti-tumor activity) and insulin secretion. Abstract : Silkworms have been reported to promote the growth and production of the stromata of C. militaris (L.) Link as a parasite insect medium and may improve its metabolites. The effects of Tussah silkmoth pupae (TG group) and rice (RG group) on the metabolic profile of C. militaris (L.) Link were compared by metabolomics. Meanwhile, the profile of natural C. sinensis (NG group) was also analyzed. The functions of these metabolites from different groups and cordycepin were tested using breast cancer cells and an animal model. 292 metabolites were detected, including 51, 31 and 23 unique metabolites from the TG, RG and NG groups, respectively. The level of 3-deoxyadenosine (cordycepin with anti-tumor activity) was highest in the TG group. Tussah silkmoth pupae induced the biosynthesis of cordycepin and unsaturated fatty acids, which may be beneficial in the prevention of breast cancer. The TG group and cordycepin had significant inhibitory activities on breast cancer cells and in animal models when compared with the two other groups. Tussah silkmoth pupae improved the metabolic profile of C. militaris (L.) Link, which has more pharmaceutical metabolites than C. sinensis .